The creation of a confidence scale: the confidence in managing challenging situations scale. (September 2021) - Walsh, Pauline; Owen, Patricia; Mustafa, Nageen
Background: Self-confidence and self-efficacy are vital psychological constructs that can affect a student's performance. Aims: To measure the level of confidence in nursing students in managing challenging situations in clinical practice settings. Methods: In order to develop the scale three focus groups were conducted: with registered nurses, third year student nurses and service users. Focus group frameworks included: challenging behaviours, managing challenging situations and preparing students to manage challenging situations. Themes in relation to challenging situations that emerged from the focus groups, in conjunction with Nursing and Midwifery Council standards and expert discussions were used to create the confidence scale. The Confidence in Managing Challenging Situations Scale consists of two parts with 21 items in total. Both parts were measured by way of a five-point Likert scale. The scale was utilised to determine the level of confidence of students both pre and post a teaching intervention. Results: The confidence in managing challenging situations scale had good internal consistency, with a Cronbach's alpha coefficient reported of 0.86. Exploratory factor analysis was used to support the scale validation process. Conclusions: The Confidence in Managing Challenging Situations Scale is a successful measure of confidence for nursing students in healthcare settings. It can be applied in alternative healthcare settings for the identification of confidence levels in those student nurses learning in care settings.